PEMANFAATAN PRINSIP KERJA SAMA DALAM KEGIATAN PEMBELAJARAN DI KELAS - Bayu Andi Mardlona; Wini Tarmini; Mulyanto Widodo (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2013)
The problem discussed in this research was the use of the principle of cooperation in the learning activities in elementary school at first grade of elementary school. The objective of this research was to describe the utilization of cooperation in the learning activities at first grade of elementary school.The method which was used in this research was qualitative-descriptive method. The technique of collecting data used simak bebas libat cakap technique. The data source in this research was teacher and students at first grade of SD Negeri 1 Trimulyo, Sekampung, Lampung Timur. Based on the result of the data analysis; found four maxims on the utilization of the principle of cooperation in the learning activities, namely quantity maxim, quality maxim, relevance maxim, and realization maxim. Based on the intensity, found the discourse which made the principle of corporation using quantity maxim 16 maxims (44,4%), quality maxim 3 maxims (0,08%), relevancy maxim 1 maxim (0,02%), realization maxim 16 maxims (44,4%). Based on those maxims, it can be known that maxims which were frequently found base on resulting the data analysis is quantity maxim and realization maxim.Key words : speech act, mode, context